SEKULARISASI DAN ISLAMISASI ILMU PENGETAHUAN - Saude, Saude (Hunafa: Jurnal Studia Islamika, 2008)
Discourse on islamization of knowledge essentially emerges from the serious concern to the failure of modern sciences to â€œgive welfare to humanityâ€. The basic problem is rooted in the philosophical framework behind modern sciences that science is free-value in that science is purely for science itself regardless of its impacts to humanity and environment. This in turn paves a way to sciences to go further without any impediment, or even without any purpose except for science itself. As a result, nature and humanity are exploited on behalf of science. Therefore, it is necessary to restore science into its proper position. Islam as a religion, which gives serious concern to knowledge and science, has views of knowledge and sciences which are different from a secular concept of science. This paper will discuss this issue.Kata Kunci : sekularisasi, islamisasi ilmu pengetahuan